Infografis sebagai Pendukung Berita In-depth dalam Situs Tirto.id - Riyanti Hayuning Pratiwi; Ferry Darmawan (MediaTor (Jurnal Komunikasi), 2019)
Tirto.id is an online news site known for its infographics. The information contained in Tirto.id is generally an in-depth report that has a long duration of written characteristics. One of the interesting news is about the looting of warship carcasses in Indonesian waters titled “The Mystery of the Dutch War shipwreck in the Java Sea” issue of January 18, 2018. The news is Mnejadi exclusive report on Tirto.id. With a fairly long writing duration. However, the presence of infographics is one way to understand long stories more easily and quickly. Using the case study method, the study aims to see infographic functions in the news in-depth. The results found are: (1) The infographic presented Tirto.id in its in-depth writing has some characteristics such as the use of more formal layouts than other news infographic layouts, the input data contains the news value, And the use of bright colors and interesting illustrations; (2) The depth of information that is presented in-depth infographics is still lacking when compared to the depth of the news itself, but between infographics and their contents is complementary unity; (3) The use of infographics in an in-depth news is nothing but a reader’s attention.